THE RELATIONSHIP OF RECENT VERTICAL MOVEMENTS TO THE MORPHOSTRUCTURAL PATTERN OF THE KAZAKH SHIELD - Finko E.A. (My University, 1992)
The geodetic data on recent vertical crustal movements within the Kazakh shields is in good correlation with its development in the Holocene (according to a study of juvenile river terraces); they point to gradual transition of the shield to the platform morphostructures of Western Siberia and a contrasting joining with the Central Asia orogenic belt. Small gradients of recent vertical movements dominate the shield. Moderate gradients are typical of local structures, whereas increased and extremely high gradients belong to active deep fault zones.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен